Other-regarding preferences and leadership styles - Martin G. Kocher; Ganna Pogrebna; Matthias Sutter (Institute for the Study of Labor (IZA), 2009)
We use a laboratory experiment to examine whether and to what extent other-regarding preferences of team leaders influence their leadership style in choice under risk. We find that leaders who prefer efficiency or report high levels of selfishness are more likely to exercise an autocratic leadership style by ignoring preferences of the other team members. Yet, inequity aversion has no significant impact on leadership styles. Elected leaders have a higher propensity than exogenously assigned leaders to use a democratic leadership style by reaching team consensus. Male leaders and leaders influenced by group membership tend to employ a democratic leadership style.
urn:nbn:de:101:1-20090330134
Keywords: C91; C92; D70; D81; 330; Leadership style; other-regarding preferences; unobserved heterogeneity; Führungstheorie; Gruppenarbeit; Soziale Beziehungen; Spieltheorie; Test